Modulation of the Neuro–Cancer Connection by Metabolites of Gut Microbiota - Alice N. Mafe; Dietrich Büsselberg (Biomolecules)
The gut–brain–cancer axis represents a novel and intricate connection between the gut microbiota, neurobiology, and cancer progression. Recent advances have accentuated the significant role of gut microbiota metabolites in modulating systemic processes that influence both brain health and tumorigenesis. This paper explores the emerging concept of metabolite-mediated modulation within the gut–brain–cancer connection, focusing on key metabolites such as short-chain fatty acids (SCFAs), tryptophan derivatives, secondary bile acids, and lipopolysaccharides (LPS). While the gut microbiota’s impact on immune regulation, neuroinflammation, and tumor development is well established, gaps remain in grasping how specific metabolites contribute to neuro–cancer interactions. We discuss novel metabolites with potential implications for neurobiology and cancer, such as indoles and polyamines, which have yet to be extensively studied. Furthermore, we review preclinical and clinical evidence linking gut dysbiosis, altered metabolite profiles, and brain tumors, showcasing limitations and research gaps, particularly in human longitudinal studies. Case studies investigating microbiota-based interventions, including dietary changes, fecal microbiota transplantation, and probiotics, demonstrate promise but also indicate hurdles in translating these findings to clinical cancer therapies. This paper concludes with a call for standardized multi-omics approaches and bi-directional research frameworks integrating microbiome, neuroscience, and oncology to develop personalized therapeutic strategies for neuro-cancer patients.